Marine algae and their bioactive compounds as novel modulators for mitochondrial quality control: from mechanism to therapeutic potential - Zhang, Chi; Yuan, Ling; Li, Jingjing; Lu, Doudou; Du, Yuhua; Nan, Yi (Frontiers in Marine Science, 2025)
Mitochondrial Quality Control (MQC) is the core mechanism for ensuring mitochondrial quality and maintaining cellular function. Marine algae and their bioactive compounds represent a huge treasure trove of natural medicines. In recent years, research on the regulation of mitochondrial biogenesis, mitochondrial dynamics, mitophagy, and mitochondrial protein balance by marine algae has continuously emerged, and their mechanisms of action have gradually become clearer. Bioactive compounds are the material basis for marine algae to exert this regulatory function. Based on their chemical structures, they can be classified into types such as marine algal polysaccharides, marine algal carotenoids, marine algal proteins, and marine algal peptides. Based on the analysis of the chemical structures of these compounds, we believe that structural differences, including planarity, degree of sulfation, and stereoisomerism, may help explain their regulatory effects on MQC. Furthermore, numerous scholars have demonstrated through preclinical studies, using animal or cell models, that marine algae and their bioactive compounds can improve muscle function, treat tumors, type 2 diabetes mellitus, and nervous system diseases, among other effects, by regulating MQC. Currently, this interdisciplinary field holds significant potential for development. This review primarily incorporates literature published between 2019 and 2025 that is highly relevant to the mechanisms of MQC regulation by marine algae and their bioactive compounds. It analyzes the latest research progress from three dimensions: mechanisms of action, molecular structures, and therapeutic applications. Furthermore, it identifies potential challenges and future research directions in the field, aiming to provide support for future drug development and treatment strategies.